Winging of Scapula due to a Sinister Etiology - Shania Niromi Gunasekera; Priyanka Yogananda; Harindra Karunatilaka; Bimsara Senanayake (Case Reports in Neurological Medicine)
Background. Scapular winging is a rare but disabling deformity, which is commonly caused by lesions of the long thoracic and spinal accessory nerves that innervate the serratus anterior and trapezius muscles, respectively. Across the literature, traumatic injury to the nerves account for the majority of cases. Less common, nontraumatic causes include viral illness, neuroinflammatory conditions, toxins, compressive lesions, and C7 radiculopathy. We present a case where an apical lung malignancy causes winging of scapula by infiltrating C5–C7 roots of brachial plexus, which has been reported only once in the literature. Case. A 54-year-old male presented with recent onset painful difficulty in raising his right arm. He had no respiratory or constitutional symptoms. On examination, winging of scapula on the right side was noted with wasting and fasciculation involving the ipsilateral shoulder girdle. Proximal muscle power of the right upper limb was of 3/5 with preserved distal muscle power. No sensory loss was noted. A patch of bronchial breathing was found in the upper zone of the right lung with multiple hard cervical lymphadenopathies. Chest X-ray and contrast-enhanced computerized tomography-chest revealed a large tumor in the upper lobe of the right lung, which was confirmed to be a carcinoma of the lung. Electromyogram revealed large motor unit potentials and poor activation of right serratus anterior and internal scapulae muscles, while nerve conduction studies concluded the presence of a compressive lesion involving C5–C7 nerve roots of brachial plexus. Histology of a biopsy of the cervical lymph node confirmed metastasis from a poorly differentiated adenocarcinoma of the lung. The patient denied further investigation with MRI cervical spine. He was transferred to the cancer institute for further treatment. Conclusion. This case highlights the value of considering a compressive lung pathology with infiltration in the differential diagnosis, when evaluating winging of scapula.